Simulation study on pollutant emission characteristics of 1000MW coal-fired boiler blended with sludge. Issue 1 (1st October 2022) - Chen, Linfeng; Li, Fangqin; Li, Kejun; Liu, Xin; Cai, Jianming
Abstract: Fluid calculation simulation software was used to simulate the sludge blending in a 1000MW coal-fired power station boiler to study the effect of different blending ratios on the generation and emission of NOx, SO2, and CO. In this paper, the total calorific value of blending is kept constant for blending. The results show that the furnace chamber temperature decreases with increasing blending ratio. NOX concentration also decreases with increasing blending ratio. SO2 and CO concentrations gradually increase at the burner nozzle of the blended sludge, and the SO2 concentration at the furnace outlet is on the rise.